Synopsis: Farmers’ grain storage and losses in Ethiopia: Measures and associates - Bachewe, Fantu Nisrane; Li, Lan; Minten, Bart; Taffesse, Alemayehu Seyoum; Pauw, Karl; Cameron, Alethia; Genye, Tirsit (International Food Policy Research Institute, 2018)
Storage losses of crops on the farm are often assumed to be an important contributor to presumed large post-harvest losses in developing countries. However, reliable and representative estimates on these losses are often lacking. We study farmers’ storage decisions and self-reported storage losses for grain crops based on two recent large-scale household surveys conducted in major grain producing areas in Ethiopia. We show that a relatively large share of grain production is stored, mainly for own consumption, and that storage technologies are rudimentary. We find that farmers’ self-reported storage losses amount to an average of 4 percent of all grains stored and 2 percent of the total harvest. These storage losses are shown to differ significantly by some households’ socio-economic characteristics and wealth and also by crop and prevailing humidity levels. We further see strong spatial heterogeneity in storage losses, being significantly higher in the southwestern part of the country. Efforts to scale up the adoption of improved storage technologies to reduce storage losses at the farm level should take into consideration these characteristics.